Circular RNA circ-ERBB2 promotes HER2-positive breast cancer progression and metastasis via sponging miR-136-5p and miR-198 - Jin-xiu Zhong (BMC, 2021)
Abstract Background Circular RNAs (circRNAs) are pivotal regulators of various human cancers and circ-ERBB2 is abnormally expressed in breast cancer cells. However, the role and mechanism of circ-ERBB2 in HER2-positive breast cancer are still unknown. Methods The circ-ERBB2 expressions in the tumor tissues of HER2-positive breast cancer patients were tested using quantitative real-time PCR. The circ-ERBB2 function was investigated by cell counting kit 8 assay, Transwell, flow cytometry and Western blot. Mechanistically, fluorescence in situ hybridization, RNA immunoprecipitation, RNA pull-down and dual-luciferase reporter gene assays were conducted to confirm the interaction between circ-ERBB2 and miR-136-5p or miR-198 in HER2-positive breast cancer cells. Results Circ-ERBB2 was elevated in the tumor tissues of HER2-positive breast cancer patients. Functionally, the interference with circ-ERBB2 repressed HER2-positive breast cancer cell proliferation, migration, invasion and accelerated cell apoptosis. Furthermore, the mechanistic analysis corroborated that circ-ERBB2 acted as a competing endogenous RNA for miR-136-5p or miR-198 to relieve the repressive influence of miR-136-5p or miR-198 on its target transcription factor activator protein 2C (TFAP2C). Meanwhile, in vivo assays further corroborated the oncogenic function of circ-ERBB2 in HER2-positive breast cancer. Conclusions Circ-ERBB2 accelerated HER2-positive breast cancer progression through the circ-ERBB2/miR-136-5p/TFAP2C axis or the circ-ERBB2/miR-198/TFAP2C axis.